The Role of PPARγ in the Transcriptional Control by Agonists and Antagonists - Tamotsu Tsukahara (PPAR Research)
In recent years, peroxisome proliferator-activated receptor gamma (PPARγ) has been reported to be a target for the treatment of type II diabetes. Furthermore, it has received attention for its therapeutic potential in many other human diseases, including atherosclerosis, obesity, and cancers. Recent studies have provided evidence that the endogenously produced PPARγ antagonist, 2,3-cyclic phosphatidic acid (cPA), which is similar in structure to lysophosphatidic acid (LPA), inhibits cancer cell invasion and metastasis in vitro and in vivo. We recently observed that cPA negatively regulates PPARγ function by stabilizing the binding of the corepressor protein, silencing mediator of retinoic acid and thyroid hormone receptor. We also showed that cPA prevents neointima formation, adipocyte differentiation, lipid accumulation, and upregulation of PPARγ target gene transcription. We then analyzed the molecular mechanism of cPA's action on PPARγ. In this paper, we summarize the current knowledge on the mechanism of PPARγ-mediated transcriptional activity and transcriptional repression in response to novel lipid-derived ligands, such as cPA.